Best Paper Award - Gregoriades, Andreas (My University, 2026)
Best paper award for the paper with title "Assessing the reliability of socio-technical systems" Andreas Gregoriades, Alistair Sutcliffe, Jae Eun Shin Modelling and tools category at the International Council on Systems Engineering (INCOSE) Las Vegas.
Keywords: Sciences